Theoretical Approaches in the Research of Inbound Tourism: the Case of Bulgaria - Скутар, Тетяна; Король, Олександр (My University, 2019)
The present work is aimed at revealing the peculiarities of structure and dynamics of inbound tourism in Bulgaria in 2007-2016. The mathematical statistics and time series method are used to analyze tourism flows. The fluctuations in arrivals to Bulgaria were explained by the dynamics of outbound tourism in the countries of origin of tourists and by other factors. The analysis of the structure of inbound tourism has shown that about half of the arrivals come from the neighbouring countries and these flows have the character of “diffusion”, as shown by the coherence of the arrivals with the length of the common land border, as well as the weak seasonal nature. Other arrivals directed from the countries with unfavourable conditions for recreation at the seaside and are concentrated in the summer period.
Keywords: international tourism flows; inbound tourism; structure of tourist arrivals; seasonality in tourism; time series; trend and deviation